Oral chemotherapy - Magoń, Małgorzata; Wiktor Jędrzejczak, Wiesław (Contemporary Oncology/Współczesna Onkologia, 2003)
The development of anticancer drugs was classically focused on intravenous rather than oral preparations. It was due to the better dose control necessary during an intensive anticancer treatment. It also prevented uncontrolled dosage change by the patient and overdose of active substance. However, there is a number of neoplasms where the increased dose intensity did not produce increased effectiveness and in these situations oral chemotherapy offers better quality of life. Also patients’ awareness increases considerably. Furthermore, quite frequently there is a need for palliative chemotherapy administered in order not to prolong life but to diminish occlusive symptoms. In all these situations oral administration of cytostatic drugs allows for outpatient carrying out of this treatment phase of. This decreases overall costs of such treatment and is better accepted by the patients. At present, in Poland oral preparations are available for cytostatics belonging to almost all major groups such as alkylating agents (cyclophosphamide, busulfan, chlorambucil, melphalan, temozolomide, lomustine), antimetabolites (methotrexate, mercaptopurin, tioguanine, capecytabine, fludarabine, cladribine, hydroxyurea), plant alkaloids (etoposide), anthracycline antibiotics (idarubicin), topoisomerase inhibitors (topotecan). This allows for not only single drug but also for combined oral chemotherapy. Besides cytostatics, hormonal anticancer drugs frequently have oral preparations. Furthermore, some of new preparations belonging to the inhibitors of oncogene products such as imatinib are also oral. This review is a reminder of oral cytostatics available for years and also describes newly introduced preparations.